PENGEMBANGAN SUPLEMEN KIMIAPEDIA BERBASIS LITERASI SAINS MATERI PERIODIK UNSUR PERIODE 1-5 - Chorina, Malisa; Hairida, Hairida; Masriani, Masriani (Universitas Tanjungpura, 2023)
This research supports to discuss the feasibility of Kimiapedia Supplements based on scientific literacy on periodic material period 1-5 in SMA Pontianak and describe the responses of teachers and students in SMA Pontianak. The form of research is research and development (RD) of the ADDIE model. Small-scale trials to 8 grade X students. Large-scale trials on 30 grade X students and 2 Chemistry teachers at school studied.Collection instruments are the evaluation sheet, the questionnaire responses of teachers and students. The results of information processing of the percentage of material suitability with a CVI value of 1, which means it is very appropriate, linguistic feasibility of 94.04%, and feasibility of graphic 86.11% with a very decent category. The results calculation of the percentage of student questionnaire responses, 86.80% small scale trials and 88.45% large scale trials, while the results of the questionnaire test Teacher responses 82.81%. That means the teacher's response and students of Kimiapedia Supplements are classified as very high.